Analysis of Transformational Leadership and Organizational Culture on the Quality of Public Services Mediated by Employee Performance in the National Narcotics Agency of North Sumatra Province - Yuni Sari Fransiska; Emi Wakhyuni; Wilchan Robain (International Journal of Management, Economic and Accounting, 2024)
The purpose of this study is to test and analyze : the influence of transformational leadership on the employee performance, the influence of organizational culture on the employee performance, the influence of transformational leadership on the quality of public services, the influence of organizational culture on the quality of public services, the influence of employee performance on the quality of public services, the influence of transformational leadership on the quality of public services in mediate employee performance, the influence of organizational culture on the quality of public services in mediate employee performance in the National Narcotics Agency of North Sumatra Province. This type of research is quantitative descriptive, the research sample is 56 people, and the data analysis uses the SEM (structural equality modeling) method. Overall, from the results and discussions in the study, it was concluded that there was a positive and significant influence between transformational leadership on the employee performance, there was a positive and significant influence between organizational culture on the employee performance, there was a positive and significant influence between transformational leadership on the quality of public services, there was a positive and significant influence between organizational culture on the quality of public services, there was a positive and significant influence between employee performance on the quality of public services, there was a positive and significant influence between transformational leadership on the quality of public services in mediate employee performance, there was a positive and significant influence between organizational culture on the quality of public services in mediate employee performance in the National Narcotics Agency of North Sumatra Province.